2016
DOI: 10.3892/ol.2016.5115
|View full text |Cite
|
Sign up to set email alerts
|

miR-223 decreases cell proliferation and enhances cell apoptosis in acute myeloid leukemia via targeting FBXW7

Abstract: Abstract. The expression of microRNA-223 (miR-233) has been investigated in various types of cancer. However, to the best of our knowledge, the expression and function of miR-223 in acute myeloid leukemia (AML) remains to be elucidated. The expression of miR-223 was measured by reverse transcription-quantitative polymerase chain reaction. Following transfection with miR-223, cell viability assays, cell apoptosis assays, western blot analysis and luciferase assays were conducted in AML cell lines. In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…Finally, miR‐223 was confirmed to be an independent prognostic factor for AML patients. Our findings were in line with previously published data, suggesting miR‐223 exerted a tumor suppressive function in AML . It was demonstrated that miR‐223 was downregulated in AML patients compared with healthy subjects.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Finally, miR‐223 was confirmed to be an independent prognostic factor for AML patients. Our findings were in line with previously published data, suggesting miR‐223 exerted a tumor suppressive function in AML . It was demonstrated that miR‐223 was downregulated in AML patients compared with healthy subjects.…”
Section: Discussionsupporting
confidence: 93%
“…It was demonstrated that miR‐223 was downregulated in AML patients compared with healthy subjects. Moreover, miR‐223 was shown to inhibit cell proliferation and enhance cell apoptosis in AML cell lines . Another research has also showed that there were significantly higher miR‐223 levels in patients with favorable prognosis, whereas patients with low miR‐223 expression levels were associated with worse outcome, by measuring miR‐223 expression in blasts from 115 AML patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations